PRODUCTION AND OPERATIONS DIRECTED TO ORGANIZATIONAL COMPETITIVENESS BY USING BEST MANAGEMENT PRACTICES - Beatriz Marcondes de Azevedo; Rolf Hermann Erdmann; Fred Leite Siqueira Campos (European Scientific Journal, ESJ, 2014)
The new global economy has stimulated new forms of organization and production process. It is up to managers to develop production capacities and adopt best practices in the pursuit of continuous improvement of operational performance. The aim of this study was to analyze the best practices of different organizations in main national and international journals in the area of POMs. Returned a portfolio of 93 practices considered benchmarking or just a good practice. We conclude that regardless of being considered world class practices or specific to certain contexts, should serve as examples to be followed in pursuit of organizational competitiveness.